(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2020)
Review of Asia-Pacific Centre of Education for International Understanding under the auspices of UNESCO in Multiple Pandemics: Beyond Covid-19 and Inequality Toward Global Solidarity, Seoul, 2020, 256 pp., 12.00 (?14,000), ISBN 979-1-155-31117-2